Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Just as the topic ask how to evaluate $$\sum_{k=1}^{\infty}\frac{(18)[(k-1)!]^2}{(2k)!}.$$

share|cite|improve this question
up vote 14 down vote accepted

Notice that $$ \frac{(k-1)!^2}{(2k)!} = \frac{\Gamma(k) \Gamma(k)}{ \Gamma(2k+1) } = \frac{1}{2k} B(k,k) = \frac{1}{2k} \int_0^1 x^{k-1} (1-x)^{k-1} \mathrm{d} x $$ Thus $$ \begin{eqnarray} \sum_{k=1}^\infty \frac{(k-1)!^2}{(2k)!} &=& \int_0^1 \left( \sum_{k=1}^\infty \frac{1}{2k} x^{k-1} (1-x)^{k-1} \right) \mathrm{d} x = \int_0^1 \frac{-\ln(1-x+x^2)}{2x (1-x)} \mathrm{d} x \\ &=& -2 \int_{-1/2}^{1/2} \frac{\ln(3/4+u^2)}{1-4 u^2} \mathrm{d} u = -2 \int_0^1 \frac{\ln((3 +u^2)/4)}{1-u^2} \mathrm{d} u = \frac{\pi^2}{18} \end{eqnarray} $$

In order to fill in on the last equality, define $$ f(t) = -2 \int_0^1 \frac{\ln\left(1 - t(1-u^2) \right)}{1-u^2} \mathrm{d} u $$ Clearly $f(0) = 0$, and we are interested in computing $f\left(\frac{1}{4} \right)$. $$ f^\prime(t) = 2 \int_0^1 \frac{\mathrm{d} u}{1 + t(1-u^2)} \stackrel{{u = \sqrt{\frac{1-t}{t}} \tan(\phi)}}{=} \int_0^{\arcsin(\sqrt{t})} \frac{2 \mathrm{d} \phi}{\sqrt{t(1-t)}} = \frac{2 \arcsin(\sqrt{t})}{\sqrt{t(1-t)}} = \\ 2 \frac{\mathrm{d}}{\mathrm{d} t} \arcsin^2(\sqrt{t}) $$ Thus $$ f\left(\frac{1}{4} \right) = \int_0^{\frac{1}{4}} 2 \frac{\mathrm{d}}{\mathrm{d} t} \arcsin^2(\sqrt{t}) = 2 \arcsin^2\left(\frac{1}{2}\right) = \frac{\pi^2}{18} $$

share|cite|improve this answer
That last step is still perhaps a little miraculous, but this looks like the way to go... – Steven Stadnicki Jan 12 '12 at 18:26
Would you please elaborate on how you got that last step? I had to approach this in a wholly different manner. – robjohn Apr 6 '12 at 12:48
@robjohn I have filled in the derivation. It might be not that different from yours. +1 on yours, by the way. – Sasha Apr 6 '12 at 15:10
@Sasha: that does look similar mod a change of variables. We also dropped to the derivative at different points. (+1) – robjohn Apr 6 '12 at 15:41

Maple gives the answer as $36 \arcsin(1/2)^2$. More generally, $$ \sum_{k=1}^\infty \frac{((k-1)!)^2}{(2k)!} t^k = 2 \arcsin \left(\frac{\sqrt{t}}{2}\right)^2$$

share|cite|improve this answer
what you mean by t – Mathematics Jan 12 '12 at 17:54
@Robert Israel: I guess there is a t^k missing on the left hand side and $36 \arcsin(1/2)^2 = \pi^2$ – Fabian Jan 12 '12 at 17:56
is there any method to evaluate it rather than using computer program? – Mathematics Jan 12 '12 at 17:59
Yes, start with Robert's power series $$F(x) = \sum_{k=1}^\infty \frac{((k-1)!)^2}{(2k)!} x^k,$$ fiddle with it to verify that it satisfies differential equation $$\bigl(4 x - x^{2}\bigr)\frac{d^{2} F (x)}{d x^{2}} + (2 - x) \frac{d F (x)}{d x} - 1 = 0$$ and solve that DE. – GEdgar Jan 12 '12 at 18:38
@Mathematics: I derive an equivalent series in this answer. – robjohn Apr 6 '12 at 12:50

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.